California State University Channel Islands Report: Qualitative Interviews with Influencers - ADV Market Research and Consulting:::::: (2023)
Objectives: I. Gather the opinions, experiences, and perceptions of influential stakeholders of California State University Channel Islands (CSUCI).II. Assess the qualitative data to determine themes among influencer perceptions of CSUCI.III. Identify areas in which misperceptions of CSUCI might be remedied and current strengths leveraged to inform operational and communication strategies to strengthen CSUCI's brand reputation.